Enhancing Science Knowledge in Early Childhood through Environmental Exploration-Based Learning Management - Sarkowi, Sarkowi; Wahid, Abd Hamid; Umami, Sri; Astriani, Siska Ana (JURNAL AL-TANZIM, 2023)
The introduction of the surrounding natural environment in the surrounding environment can attract the attention or interest of children with the media around them. This study aims to analyze and find out how nature-based learning management with an exploratory approach can increase scientific knowledge in students. The research method in this study uses a qualitative method with a case study type. This research was conducted at the Harapan Insan Kamil Kindergarten institution, located on the coast of Randutatah village, Probolinggo Regency. To get an overview of the object, the researcher made observations at the location and interviewed several components of the school, including the principal, two teachers at Harapan Insan Kamil Kindergarten, and two student guardians. The study results show that the management concept of the surrounding environment exploration approach in increasing scientific knowledge is carried out using program planning, implementation, and evaluation systems. The implications obtained through an exploratory environmental management approach can develop students' scientific knowledge, displayed through imaginative pictures and storytelling. Hence, this research improves students' science, carried out with environmental exploration techniques.